Effects of communities' knowledge and perception on conservation within Turfloop Nature Reserve, Limpopo Province, South Africa - Mothapo, Mabatho Valencia (My University, 2021)
Nature reserves generate substantial local income through tourism, provide opportunities for recreation and employment and aid in the protection of wildlife, biodiversity, and natural resources. In South Africa, the protection and management of nature reserves are generally done through a protectionist approach whose rigid enforcement of laws excludes access and involvement of local communities, who are a crucial stakeholder for successful wildlife management and conservation. How then do the local communities perceive nature reserves, and how does this affect nature conservation? To answer this question, this study examines the effects of communities’ knowledge and perception of nature conservation in Turfloop Nature Reserve (TNR), in Limpopo Province of South Africa. Mixed method of qualitative and quantitative techniques was used in the study to collect the data from 196 respondents in 9 local communities living within a radius of 4km from TNR. Key informant’s in-depth interviews were conducted with TNR management and community leaders. Several demographic, socio-economic and spatial variables of the local people that included education level, distance, and period of residence in the area (amongst others) were found to significantly influence knowledge and perceptions of the local people towards the TNR conservation activities. Study findings suggest that although local people appreciate the nature reserve and its role in conserving nature and wildlife, there is evidence of dislike and unfavorable perceptions towards some management activities of TNR. The unfavorable perceptions that some community members had were attributed to the absence of participation of the local people in the management of the nature reserve, access to and use of resources from the nature reserve and lack of tangible benefits from the reserve. Positive perceptions were attributed to the benefits received from TNR, such as support for educational programmes, sustainable harvest, and recreation opportunities. Therefore, this study recommends that local people should be involved in the management activities and decision making within TNR and benefits should be increased so that local people may support conservation.
Thesis (M.Sc. (Geography)) -- University of Limpopo, 2021
Keywords: Local communities; Conservation; Protected areas; Benefits; Perceptions; Nature conservation; Natural areas